2020
DOI: 10.1177/0954405420958856
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for precision manufacture of a nozzle using hybrid laser powder-bed fusion: A case study

Abstract: This paper presents a methodology for precision manufacture of a nozzle using the hybrid laser powder-bed fusion (L-PBF) technology. A new distortion predictive model for hybrid L-PBF was developed using finite element techniques. The model was validated against experimentally measured distortion using optical scanning. The validated model was utilised to mitigate distortion by applying additional stiffeners to the nozzle geometry where the distortion was reduced by 60% to acceptable tolerance of ± 200 µm. Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Relative to the as-built surfaces (having average values for Ra and Sa of 11.4 µm and 14.9 µm, respectively), these Ra and Sa values after the in-envelope micro-milling of the 316LSS surfaces were more than an order of magnitude lower and similar to finish qualities achievable on polished surfaces [47,48]. It is noteworthy that Afazov et al [21] reported minimized Ra values between 0.55 µm and 0.65 µm when using optimized milling parameters on an out-of-envelope system (i.e., Kern Evo Ultra-Precision CNC Machine) to machine 316LSS samples as-built using a Matsuura LUMEX Avance-25 system. The comparable roughness attained in the present study demonstrates the good capability, processing flexibility, and high efficacy possible with in-envelope hybrid processing.…”
Section: Printed Geometry Versus Cad Model Qualificationmentioning
confidence: 78%
See 2 more Smart Citations
“…Relative to the as-built surfaces (having average values for Ra and Sa of 11.4 µm and 14.9 µm, respectively), these Ra and Sa values after the in-envelope micro-milling of the 316LSS surfaces were more than an order of magnitude lower and similar to finish qualities achievable on polished surfaces [47,48]. It is noteworthy that Afazov et al [21] reported minimized Ra values between 0.55 µm and 0.65 µm when using optimized milling parameters on an out-of-envelope system (i.e., Kern Evo Ultra-Precision CNC Machine) to machine 316LSS samples as-built using a Matsuura LUMEX Avance-25 system. The comparable roughness attained in the present study demonstrates the good capability, processing flexibility, and high efficacy possible with in-envelope hybrid processing.…”
Section: Printed Geometry Versus Cad Model Qualificationmentioning
confidence: 78%
“…Relative to the as-built surfaces (having average values for Ra and Sa of 11.4 µ m and 14.9 µ m, respectively), these Ra and Sa values after the in-envelope micro-milling of the 316LSS surfaces were more than an order of magnitude lower and similar to finish qualities achievable on polished surfaces [47,48]. It is noteworthy that Afazov et al [21] reported minimized Ra values between 0.55 µ m and 0.65 µ m when using optimized mill- For the as-built vertical side-wall surfaces, the roughness parameters (Table 1) showed a minor dependence on the laser power over the process window studied in this work, namely with the contour E density ranging from 19.0 J•mm −3 to 45 J•mm −3 . The surface roughness on the as-printed vertical side-walls exhibited Sz values of 144.77 µm and 106.4 µm, respectively, at the lowest and highest conditions of 160 W (19.0 J•mm −3 ) and 380 W (45 J•mm −3 ).…”
Section: Printed Geometry Versus Cad Model Qualificationmentioning
confidence: 80%
See 1 more Smart Citation
“…Little research has been conducted into modelling hybrid LPBF and micro-milling. Afazov et al [115] used the inherent strain approach for modelling LPBF and further developed the inclusion of the micro-milling process. The material removal process was modelled by deactivating elements form the stiffness matrix, in a similar fashion to the modelling of conventional machining.…”
Section: Machining Operationsmentioning
confidence: 99%
“…Modelling of hybrid LPBF for a stainless steel 316 component. The figure shows a comparison of experimentally measured surface deviation from the nominal geometry and that predicted numerically[115]. Units in mm…”
mentioning
confidence: 96%